Kapangyarihang bayan sa pagkain People's food sovereignty (Manila, Philippines IBON Foundation, Video Production Unit, 2005)
The ultimate recognition of the people's right to food is the recognition of their right to produce food, which entails the recognition of their right as food producers to access resources for production.In the midst of worsening global hunger, the aim of people's food sovereignty is to combine people power and human rights in order to unite the people in asserting and realizing their right to food.